A peace to end all peace : (Avon Books, 2000)
Contents: At the crossroads of history; Kichener of Khartoum looks ahead; Britain is drawn into the Middle Eastern Quagmire; Subversion; The allies at the Nadir of their fortunes; New worlds and promised lands...